Legal Framework Analysis of Islamic Religious Education Policy Implementation - Tobroni; Abu Bakar, M. Yunus; Firmansyah, Eka; Abdeljelil, Moncef Ben (NAJAHA, 2024)
This study examines the harmonization of national legal frameworks with the Islamic education system at Al-Istiqamah Modern Islamic Boarding School Ngatabaru using a comprehensive juridical-empirical case study methodology. Employing a qualitative approach, the research systematically explored the intricate relationship between national education regulations and institutional practices through a multi-method data collection strategy. The research methodology employed three primary techniques: in-depth interviews with diverse stakeholders (school leadership, teachers, administrative staff, education supervisors, and student representatives), extensive document analysis of national education regulations and internal school policies, and comprehensive field observations. This approach captured nuanced perspectives on policy implementation and provided a structured framework for understanding legal and institutional dynamics. Findings revealed a sophisticated approach to harmonizing national legal frameworks with Islamic educational systems. The boarding school achieved 83% compliance with national education standards through strategic curriculum integration, with an innovative quality assurance system driving educational improvements. This was evidenced by a 15% increase in national examination scores and an 85% stakeholder satisfaction rate. The study identified critical policy harmonization challenges, including learning time allocation, evaluation system alignment, and teacher competency development. The boarding school responded with adaptive strategies featuring an integrated learning system and targeted teacher professional development programs. The research's significance is highlighted by graduate performance outcomes, with 80% accessing prestigious universities and 75% entering the workforce within one year of graduation. This provides a comprehensive analysis of educational policy implementation in modern Islamic boarding school contexts.